2007
DOI: 10.1111/j.1365-2842.2006.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nociceptive trigeminal inhibitory splint on electromyographic activity in jaw closing muscles during sleep

Abstract: The nociceptive trigeminal inhibitory (NTI) splint has been claimed to decrease the electromyographic (EMG) activity of jaw-closing muscles and relieve symptoms of various types of temporomandibular disorders (TMD) and bruxism. The present study was designed to address the question about EMG-changes during sleep. Ten patients (age: 23-39 years) with a self-report of tooth-grinding during sleep were recruited. Patients were examined at baseline and after each treatment period with the use of the Research Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 15 publications
(26 reference statements)
3
79
0
1
Order By: Relevance
“…Baad-Hansen et al [30] found a significant reduction in EMG activity in the masseter during sleep when patients used nociceptive trigeminal inhibitory (NTI) splint and, curiously, found no significant reduction in EMG activity in the masseter during sleep when patients used a standard occlusal splint, which converge to our findings using the same type of device. Conversely, the reduction in masseter EMG using NTI was not associated with a reduction in signs or symptoms of the patients.…”
Section: Discussionsupporting
confidence: 86%
“…Baad-Hansen et al [30] found a significant reduction in EMG activity in the masseter during sleep when patients used nociceptive trigeminal inhibitory (NTI) splint and, curiously, found no significant reduction in EMG activity in the masseter during sleep when patients used a standard occlusal splint, which converge to our findings using the same type of device. Conversely, the reduction in masseter EMG using NTI was not associated with a reduction in signs or symptoms of the patients.…”
Section: Discussionsupporting
confidence: 86%
“…Each patient received both splints and the study lasted 7e8 weeks including the washout period. The authors concluded that the significant decrease of EMG activity is not associated with a reduction in temporomandibular disorders' signs or symptoms, once 5 of 10 patients perceived pain at baseline (Baad-Hansen et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…8 The influence of cerebral circuits on occlusal movements is unknown, and it has been suggested that possible benefits of an occlusal splint arise from the presence of a foreign object, consciousness or cerebral learning. 9,10 MRI is a sophisticated technique that presents structural anatomy of the brain with high spatial resolution. Functional MRI (fMRI) provides anatomical data in addition with functional data.…”
Section: Introductionmentioning
confidence: 99%